2012
DOI: 10.1039/c2jm35437c
|View full text |Cite
|
Sign up to set email alerts
|

Organic dual-wavelength distributed feedback laser empowered by dye-doped holography

Abstract: An organic dual-wavelength distributed feedback (DFB) laser empowered by a dye-doped holographic polymer dispersed liquid crystal (HPDLC) grating is reported for the first time. The dualwavelength laser operates at 586.6 nm and 670.2 nm simultaneously in one laser beam via the seventh and eighth Bragg orders of a one dimensional (1D) HPDLC grating with a special period. We theoretically and experimentally demonstrate the mechanism of our dual-wavelength DFB laser and investigate the threshold and spectral prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…But the employed organic dye solution leads to the huge difficulty to meet the requirements of flexible and miniature devices. Recently, main efforts are focused on the tunable organic solid‐state lasers . For example, Klinkhammer et al have reported an outstanding method that can continually tune the lasing wavelength of the distributed feedback laser device .…”
Section: Introductionmentioning
confidence: 99%
“…But the employed organic dye solution leads to the huge difficulty to meet the requirements of flexible and miniature devices. Recently, main efforts are focused on the tunable organic solid‐state lasers . For example, Klinkhammer et al have reported an outstanding method that can continually tune the lasing wavelength of the distributed feedback laser device .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, Diao et al reported the dual-wavelength lasing from the semiconducting film and the doped dye using the HPDLC as oscillation cavity [17]. Zhang et al demonstrated the surface-emitting dual-wavelength laser from a blended gain layer using two semiconducting polymer [18].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-wavelength OSSLs are useful and promising devices, especially in the field of communications [ 15 ] and lab-on-a-chip [ 16 ], since multi-wavelength lasing can be achieved with one smart laser. To achieve this goal, Diao et al reported the dual-wavelength lasing from the semiconducting film and the doped dye using the HPDLC as oscillation cavity [ 17 ]. Zhang et al demonstrated the surface-emitting dual-wavelength laser from a blended gain layer using two semiconducting polymer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Bragg equation and DCM gain property, this period will allow the third DFB laser emission occurrence at $625 nm, which falls in the center of the DCM gain spectrum. 24) A power supply was used to apply an electric field (rectangular signal: 1 kHz frequency) to continuously control the orientation of the LCs when the sample was being optically pumped by a 532 nm Q-switched neodymium-doped yttrium aluminum garnet (Nd:YAG) pulsed laser (pulse duration: 8 ns; repetition rate: 8 Hz). The electrically tunable lasing output was detected by a fiber-coupled spectrometer, and a polarizer was placed before the fiber to allow only TM laser emission to be collected.…”
mentioning
confidence: 99%